Evaluation of the use of Idesia polycarpa Maxim protein coating to extend the shelf life of European sweet cherries - Yang, Wenqing; Zhang, Zimu; Chen, Yaobing; Luo, Kai (Frontiers in Nutrition, 2023)
Idesia polycarpa Maxim protein was used as a substrate to prepare a novel food packaging material with bioactive functions for encapsulating and extending the postharvest shelf life of sweet cherries. The film-forming solution was prepared from a mixture of Idesia polycarpa Maxim protein, glycerol, and gelatin, and was cast to form a film at room temperature and evaluated for mechanical, optical, structural, crystallinity, thermal properties, morphology, and antioxidant activity. Idesia polycarpa Maxim protein composite film solution was applied as an edible coating on sweet cherries and evaluated for changes in physical and biochemical parameters of sweet cherries in storage at 20 ℃ and 50% relative humidity for 9 days. The results showed that the film tensile strength increased from 0.589 to 1.981 Mpa and the elongation at break increased from 42.555% to 58.386% with the increase of Idesia polycarpa Maxim protein concentration. And in the in vitro antioxidant assay, IPPF-4.0% was found to have the best antioxidant activity, with scavenging rates of 65.11% ± 1.19%, 70.74% ± 0.12%, and 90.96% ± 0.49% for DPPH radicals, ABTS radicals, and hydroxyl radicals, respectively. Idesia polycarpa Maxim protein coating applied to sweet cherries and after storage at 20 ℃ and 50% relative humidity for 9 days, it was found that the Idesia polycarpa Maxim protein coating significantly reduced the weight loss (54.82% and 34.91% in the Control and Coating-2.5% groups, respectively) and the loss of ascorbic acid content (16.47% and 37.14% in the Control and Coating-2.5% groups, respectively) of the sweet cherries, which can effectively extend the aging of sweet cherry fruits and prolong their shelf life. The developed protein film of Idesia polycarpa Maxim with antioxidant activity can be used as a new food packaging material in the food industry.